Migrant Women of Johannesburg: Life in an in-between City - Kihato, Caroline. (Wits University Press, 2013)
Johannesburg is filled with many migrants from across Africa and the world, seeking opportunities in the ‘city of gold’. In this book, Caroline Wanjiku Kihato, who began her life in South Africa as a street trader, uses narratives and images to explore the lives of women from Cameroon, the Democratic Republic of Congo, Congo Brazzaville, Nigeria, Rwanda, Burundi, Kenya, Tanzania, Uganda and Zimbabwe, now living in Johannesburg. Using their stories of love, illness, fears, children, violence, family and money, she explores women’s relationships with host and home communities, the South African state, economy and the city of Johannesburg.
Keywords: Migrant Women